Analisis Promosi dalam Strategi Pengembangan Usaha Tahu Lestari Desa Simangambat Kecamatan Siabu Kabupaten Mandailing Natal - Hofifah Hofifah; Ade Khadijatul Z Hrp; Arwin Arwin (Jurnal Inovasi Ekonomi Syariah dan Akuntansi, 2024)
This research was carried out on the basis of describing promotion analysis in the development strategy of a sustainable tofu trading business in Simangambat village, Siabu sub-district, Mandailing Natal district by taking a case study in Simangambat village, Siabu sub-district, Mandailing Natal regency, which is one of the villages whose community has a tofu trading business, namely Sustainable tofu. This research was conducted from October 2023- July 2024. This research method uses a qualitative approach where this research describes, explains and interprets objects according to what they are. Data validation was carried out by gathering information from several informants who were directly related to the Tofu Trading Business. Apart from that, the researcher also carried out direct observations at the research location to verify the data whether the data obtained from the informants was in line with reality data or not. As a result of this research, the author concludes that the promotion analysis in the development strategy for the sustainable tofu trading business in Simangambat village still cannot be said to be optimal. This can be seen from the marketing system of tofu factories which has not kept up with the times and is still developing a system through a system of entrusting it to stalls. So sustainable tofu businesses must develop systems such as using social media for marketing so that the business they manage can develop further and can also compete with other tofu businesses.